Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan Terhadap Nilai Perusahaan - Wicaksana, Fahmi Adrian Wira; Suwarno, Suwarno (Universitas Muhammadiyah Gresik, 2024)
This study aims to examine the effect of Capital Structure, Profitability, and Company Size on the Value of Companies engaged in the automotive sector which listed on the Indonesia Stock Exchange during 2018-2020. This research itself uses quantitative methods and uses secondary data as a source of data to be processed. The technique used in this research is purposive sampling and obtained a sample of 84 from 28 LQ45 companies. The data used in this study is secondary data form the documents.Data analysis using multiple linear regression analysis. The results of this study indicate that the capital structure has no effect on firm value. Profitability has a positive and significant affect on firm value. Firm size has no effect on firm value. Type of Paper: Empirical Keywords: Capital Structure,Profitability,Firm Size,Firm Value.